The Benchmarking Practices of the Economically Freest Countries in Europe and the World - Rožans, Edgars (Ekonomika, 2016)
In our increasingly globalised economy, global competitiveness of countries and the means to measure it gain increasing significance. One of the ways to measure global competitiveness is by comparing an extent of the economic freedom that a country has, which also can, as surveys show, largely explain differences in living standards across the world. Seeing as how European economy is similar to most of the Western world capitalist economies in the sense that it has, for a number of reasons, very different economic policy traditions than many countries in other parts of the world, we may approach this topic from a European perspective; consequently, we can see that the main hypothesis of the work can be confirmed, and it is possible, for reasons based in economic or national image nature, to discern which is the freest of world economies by adopting the benchmarking practices of the continent. Nevertheless, the other hypothesis of the work does not fulfill itself, meaning that by adopting taxing policies of some of the wealthiest European Union economies it is not possible anymore to reach the result of the freest economy, both in the world and particularly Europe. Looking at the components and scores of the Index of Economic Freedom, it becomes apparent that the inclusion of government share components in its methodology is very controversial, similarly as the labour freedom component and even monetary freedom, albeit in lesser extent.
Keywords: Economic freedom and its components; competitiveness; The Index of Economic Freedom